Vrednotenje naravnih in družbenih dejavnikov za potrebe sonaravnega razvoja s pomočjo geografskih informacijskih sistemov - Ciglič, Rok (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
Planning the locations in areas with various types of land use is complicated and important work. It requires extensive knowledge of natural and social conditions and, also, the presentation of results in illustrative and understandable manner. This article defines the most suitable uninhabited areas for potential settlement in the Kočevje municipality with respect to natural and social factors. Geographical information systems were used for the analysis.
Keywords: geografski informacijski sistemi; Kočevje; naselja; prostorsko planiranje; regional geography; regionalna geografija; spatial planning; sustainable development; trajnostni razvoj